Regioselective Synthesis of α‐Fluorinated Cyclopentenones by Organocatalytic Difluorocyclopropanation and Fluorine‐Directed and Fluorine‐Activated Nazarov Cyclization. Issue 12 (27th January 2017) - Fuchibe, Kohei; Takayama, Ryo; Yokoyama, Takaharu; Ichikawa, Junji
Abstract: Silyl dienol ethers, prepared from α, β‐unsaturated ketones, underwent proton sponge‐catalyzed difluorocyclopropanation with trimethylsilyl 2, 2‐difluoro‐2‐fluorosulfonylacetate in a regioselective manner, leading to 1, 1‐difluoro‐2‐siloxy‐2‐vinylcyclopropanes in good yields. The cyclopropanes thus obtained were in turn subjected to fluoride‐ion‐catalyzed ring opening to afford 1‐fluorovinyl vinyl ketones (i.e., Nazarov precursors). Treatment of the precursors with Me3 Si + B(OTf)4 − regioselectively promoted the Nazarov cyclization, the rate and regioselectivity of which were drastically enhanced by the fluoro substituent, which thus facilitated efficient synthesis of biologically promising α‐fluorocyclopentenone derivatives. Abstract : Director and activator : Silyl dienol ethers underwent proton sponge‐catalyzed difluorocyclopropanation with TFDA in a regioselective manner to give 1, 1‐difluoro‐2‐siloxy‐2‐vinylcyclopropanes, fluoride‐catalyzed ring opening of which afforded 1‐fluorovinyl vinyl ketones (i.e., Nazarov precursors). Treatment of the precursors with Me3 Si + B(OTf)4 − led to fluorine‐directed/activated Nazarov cyclization and gave biologically promising α‐fluorocyclopentenone derivatives (see scheme).